Intention to Reuse E-Learning among GENBI Students - Williansyah, Yofie; Abdillah, Willy; Fachruzzaman, Fachruzzaman (Universitas Bengkulu, 2024)
The e-learning lecture system is an important innovation in the world of education, allowing students to study remotely via the internet. The positive impact of e-learning learning is that students become more responsible and can value their time. Intention to Reuse is a person's Intention to Reuse a system that has been implemented in a higher education environment. This research aims to determine the influence of perceived usefulness, perceived convenience, subjective norms and IT system quality on Intention to Reuse. This research is a type of descriptive research with a quantitative approach (survey). The type of data used is primary data obtained through distributing questionnaires. The respondents of this research were 195 GENBI students at UNIB, UIN, UMB, and IAIN Curup. The data analysis technique used multiple linear regression analysis with the help of the SPSS 25 application. The research results are (1). Perception of usefulness has a positive and significant effect on Intention to Reuse. This perception of usefulness impacts students' Intention to Reuse. (2). Perception of convenience has no effect on Intention to Reuse, this perception of ease has no impact on Intention to Reuse. (3) Subjective Norms has a positive and significant effect on Intention to Reuse. (4) Perception of IT quality has a positive and significant effect on Intention to Reuse. This means that the quality of the IT system impacts students' Intention to Reuse. Suggestions for future research include adding samples other than Genbi students and adding other variables, such as organizational culture and perceptions of trust